KONSEP KEWAHYUAN AL-QUR’AN DALAM KACAMATA WILLIAM MONTGOMERY WATT - Habibuddin dan Ihdi Aini (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2020)
ABSTRACT William Montgomery Watt was born on March 14, 1909 in Ceres, Fife, Scotland. An expert in Islamic studies from Great Britain, and one of the main orientalists and historians of Islam in the Western world. One of his works that is quite controversial and phenomenal is Islamic Revelation in The Modern World. This book is not purely academic, but also contains personal elements of reflection on his observations about the relationship between Islam and Christianity. Discussing the concept of revelation in Islam and related matters, Christianity and Islam have the same basis, that all have a teaching or mission to the modern world. Therefore, knowledge does not directly compare Christian and Islamic thought, but connects them with the secular and neutral world and combines them with a scientific perspective. Based on his neutral attitude in seeing the two major religions, Watt concluded that what actually happened, namely the conflict between Islam and Christianity, was simply a misperception of each other. Because of his neutrality, Watt can be classified as an orientalist who is honest in seeing Islam. He tried to see the Qur'an from a modern scientific perspective and did not take sides with Christianity. Therefore, the Qur'an which he discussed for centuries must be studied further by following a new path. And this is a big job that both Muslims and non-Muslims must do. Compared to others W. Montgomery Watt is an orientalist who does not discredit Islam, nor does he deny other religions. Watt through his arguments tried to make anti-Islamic orientalists realize that the revelation brought by Muhammad really came from Allah and was not an invention of his own. Watt introduced the theory of the subconscious which was conveyed by Gabriel and then it radiated through the conscious mind.